2015
DOI: 10.1002/jbmr.2527
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Myocardial Infarction Upregulates Circulating Fibroblast Growth Factor-23

Abstract: Myocardial infarction (MI) is a major cause of death worldwide. Epidemiological studies have linked vitamin D deficiency to MI incidence. Because fibroblast growth factor‐23 (FGF23) is a master regulator of vitamin D hormone production and has been shown to be associated with cardiac hypertrophy per se, we explored the hypothesis that FGF23 may be a previously unrecognized pathophysiological factor causally linked to progression of cardiac dysfunction post‐MI. Here, we show that circulating intact Fgf23 was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 48 publications
4
75
1
Order By: Relevance
“…At that time, FGF23 was majorly considered to be regulated by other CKD-MBD components, such as high vitamin D, high parathyroid hormone and high phosphorus [21]. In contrast, we learnt in recent years that regulators outside such classical CKD-MBD pathways (in the following referred to as "non-CKD-MBD regulators") may substantially contribute to FGF23 regulation, among which iron deficiency [22] and prevalent heart disease [23] may be of particular importance.…”
Section: Strength Of Fibroblast Growth Factor 23 As a Cardiovascular mentioning
confidence: 97%
See 1 more Smart Citation
“…At that time, FGF23 was majorly considered to be regulated by other CKD-MBD components, such as high vitamin D, high parathyroid hormone and high phosphorus [21]. In contrast, we learnt in recent years that regulators outside such classical CKD-MBD pathways (in the following referred to as "non-CKD-MBD regulators") may substantially contribute to FGF23 regulation, among which iron deficiency [22] and prevalent heart disease [23] may be of particular importance.…”
Section: Strength Of Fibroblast Growth Factor 23 As a Cardiovascular mentioning
confidence: 97%
“…FGF23 may reflect prevalent cardiovascular disease [2]. This concern has been founded upon the observation that hypertrophic and failing [20,23,28] hearts may directly produce FGF23, that particularly high FGF23 levels are found in patients with severe acute heart disease [38,39], and that patients chronically exposed to high FGF23 -such as patients with hypophosphatemic rickets/osteomalacia -do not regularly develop heart disease [40]. Experimentally, a direct role of FGF23 in the development of vascular calcification has largely been ruled out [41], and data on its contribution to left ventricular hypertrophy remains uncertain: even though several reports have suggested FGF23 to activate cardiomyocytes and induce their proliferation [8,9], later studies have questioned these findings [15][16][17][18][19][20].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…It should be noted, however, that Andrukhova et al also showed in their animal study that serum FGF23 increased 2-4 weeks after reperfusion. 15 Last, we cannot conclude which of the 3 observations (i.e., absolute value of FGF23 on admission, absolute value on day 7, and relative FGF23 increase on day 7) will have the most significant clinical importance, because, in the current study, only a small number of patients was enrolled, and whether or not the serum FGF23 level on admission was decreased among patients with AMI could not be definitively determined.…”
Section: Study Limitationsmentioning
confidence: 76%
“…In an animal model of MI and subsequent reperfusion, elevation of the serum FGF23 level was demonstrated at 2-and 4-weeks post-MI, although whether or not it had changed at earlier time points was not reported. 15 These findings collectively raise the possibility that the alteration in the serum FGF23 level may be related to various cardiac injury or hemodynamic alterations.…”
Section: Comparison With Propensity Score Matched Non-ami Cardiac Patmentioning
confidence: 98%
See 1 more Smart Citation